THE PHILOSOPHICAL CONTEXT OF MODERN MEDICAL KNOWLEDGE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The worldview of medical specialists - their philosophical training - is an important factor in the development of the healthcare system. Humanities disciplines in medical high schools strengthen the worldview base of future doctors. Since the main front for doctors is not only the treatment of diseases, and not just the recovery of the body of patients, but above all - it is the work of consciousness, thought and impact on the soul of patients. Therefore, the philosophical base of medical knowledge remains relevant as in ancient times. He who thinks correctly - he treats diseases correctly. The modern approach to medical knowledge is of great socio-psychological importance in the context of increasing risks of a complex nature: epidemiological, geopolitical, economic and environ-mental. A modern physician is required to have comprehensive intellectual and cultural training in the face of radical global changes.
Keywords: philosophical worldview, philosophical base, credentialism, apodictic method, conventionalism, the lines of Hippocrates, Avicenna, Paracelsus and Galen.